Fresh and Post-Thaw Seminal Attributes of Jafarabadi Buffalo Bulls - Parmar, KH; Kavani, FS; Patbandha, TK; Parikh, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study was conducted on four Jafarabadi breeding bulls, 5-6 years old to know the fresh and post-thawed seminal characteristics based on total of 192 semen ejaculates evaluated and cryopreserved over one year period. The mean values of fresh neat seminal characteristics of Jafarabadi bulls, viz., ejaculate volume (ml), colour/density (score), sperm concentration (million/ml), mass activity (score), initial motility (%), live sperm (%), abnormal sperm (%), HOS reactive sperm (%) and acrosomal integrity (%) were 5.19±0.18, 2.38±0.10, 1253.36±24.75, 3.73±0.05, 80.31±0.05, 86.20±0.64, 5.00±0.40, 85.75±0.43 and 93.56±0.56, respectively, whereas the mean post-thawed sperm characteristics, viz., progressive sperm motility, live sperm (%), abnormal sperm (%), HOS reactive sperm (%), acrosomal integrity (%) and first insemination conception rate (%) observed were 57.60±0.36, 66.34±0.53, 8.85±0.33, 56.97±0.46, 75.26±0.17 and 44.63±0.14, respectively. The semen quality of fresh and post-thawed samples observed was within normal limit for use in breeding program with satisfactory first insemination conception rate